(x+8)*10=(x+6)*4

Simple and best practice solution for (x+8)*10=(x+6)*4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)*10=(x+6)*4 equation:



(x+8)*10=(x+6)*4
We move all terms to the left:
(x+8)*10-((x+6)*4)=0
We multiply parentheses
10x-((x+6)*4)+80=0
We calculate terms in parentheses: -((x+6)*4), so:
(x+6)*4
We multiply parentheses
4x+24
Back to the equation:
-(4x+24)
We get rid of parentheses
10x-4x-24+80=0
We add all the numbers together, and all the variables
6x+56=0
We move all terms containing x to the left, all other terms to the right
6x=-56
x=-56/6
x=-9+1/3

See similar equations:

| y−3=−9 | | 7b-6=6b-7 | | 7m-1+6m=8m-7m-13 | | -4x+3x+-x—11-17x=16 | | 3x+47-47=116-47 | | d=24•4 | | 1.2=x+3 | | 4x^2+100x+25=0 | | 5c-8+3-2c=16 | | -3x-32=-26 | | 20w=2L | | X+5=9x-25 | | 14.76-12.5x=-96.24 | | x=-31/2= | | 15m+6m+-2=-19 | | 4x+100=152 | | 23x-(-6.3)=236.3 | | x/10+25=-72 | | 3x–9=(-18) | | 2(27-10x)=18-2x | | 144+36=c^2 | | 12w=2L | | 0.1x0.2=0.02 | | 0.3a+1.38=0.24a+1.2 | | X/3-5/3+x/2=5 | | -30=a-10 | | 40+x/3=19 | | 0=3x/2-12 | | 15000=12000*100,005^x | | 60=3x-2(4x-5) | | 9x-32=3x-10 | | F(x)=3x-2/2x+3 |

Equations solver categories